School Efforts to Address Bullying Behavior Among Students - Azis, Lasman; Harahap, Ainun Mardia; Budio, Sesra; Husen, Amir; Islahuddin (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2024)
The role of the school is very strategic in determining the good or bad atmosphere of student socialization in the school environment, one of the things that damages socialization among students is the emergence of bullying behavior, therefore bullying behavior must be clean from the school environment. Therefore, the school is the main actor in overcoming the problem of bullying so that bullying does not become a culture among students. This study aims to analyze how the role of the school in overcoming bullying behavior that occurs among students of Islamic educational institutions. This study uses a qualitative method with a case study approach, data sources are taken through individual interviews with four informants consisting of the principal and vice principal of student affairs and infrastructure and the teacher council. All informants were selected using purposive sampling techniques. The author also collected data through direct observation and document analysis. All data were analyzed using interactive techniques of miles and huberman. The research findings indicate four school efforts to address bullying among students: i) increasing communication between teachers and students, ii) providing education about the dangers of bullying, iii) evaluating programs specifically addressing bullying, and iv) providing guidance to both perpetrators and victims of bullying. These findings can serve as examples for other schools on how to address bullying among students, ensuring that bullying does not become a part of the school culture.